Problematika Literasi dan Pembentukan Karakter Anak Usia Sekolah Dasar di Era Digital dalam Perspektif Pendidikan Agama Islam - Rifa Ardian Fahreza; Zakia Lutfiah Khoirun Nisa; Adinda Marsha Dwi Sukma; Suprapti Suprapti (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study aims to analyze literacy challenges and character development issues among elementary school students in the digital era from the perspective of Islamic education. A qualitative approach was employed through a library research method by examining various scientific publications related to literacy, character education, digital culture, the alpha generation, and Islamic educational values. Data sources consisted of academic journals, books, and relevant scholarly articles selected based on predetermined inclusion criteria. The analysis revealed that literacy problems are influenced by multiple interconnected factors, including students’ reading habits, teachers’ literacy competencies, parental involvement, and the increasing exposure of children to digital technology. In addition, the widespread use of digital media has contributed to challenges in fostering responsibility, self-control, and moral awareness among children. To address these issues, this study proposes the Islamic Character-Based Literacy Model (LIBSI), which integrates three core components: role modeling, habit formation, and digital guidance. The model is further supported by the principles of Islamic Digital Citizenship that emphasize ethical behavior, responsibility, and spiritual awareness in digital environments. Several strategic recommendations are generated from the model, including strengthening Islamic value-based digital literacy, enhancing teachers’ literacy competencies, promoting family literacy programs, and encouraging the constructive use of technology in learning activities. The LIBSI model is expected to serve as a conceptual framework for improving literacy skills while simultaneously nurturing students’ moral, social, and spiritual character in the contemporary digital era.